2015
DOI: 10.1111/nph.13621
|View full text |Cite
|
Sign up to set email alerts
|

Guard cell hydrogen peroxide and nitric oxide mediate elevated CO2‐induced stomatal movement in tomato

Abstract: SummaryClimate change as a consequence of increasing atmospheric CO 2 influences plant photosynthesis and transpiration. Although the involvement of stomata in plant responses to elevated CO 2 has been well established, the underlying mechanism of elevated CO 2 -induced stomatal movement remains largely unknown.We used diverse techniques, including laser scanning confocal microscopy, transmission electron microscopy, biochemical methodologies and gene silencing to investigate the signaling pathway for elevated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(68 citation statements)
references
References 68 publications
2
66
0
Order By: Relevance
“…Silencing of OST1 and RBOH1 in tomato reduces H 2 O 2 and NO accumulation in response to elevated CO 2 levels, whereas silencing NR only reduces the accumulation of NO. These findings indicate that OST1 and NADPH oxidase‐dependent H 2 O 2 production act upstream of NO production during CO 2 signaling in guard cells (Shi et al ). Together, these findings suggest that ABA and ROS signaling are required to enhance high CO 2 ‐induced stomatal closure.…”
Section: Crosstalk Among Co2 Aba and Ros Signaling During Stomatal Mmentioning
confidence: 90%
“…Silencing of OST1 and RBOH1 in tomato reduces H 2 O 2 and NO accumulation in response to elevated CO 2 levels, whereas silencing NR only reduces the accumulation of NO. These findings indicate that OST1 and NADPH oxidase‐dependent H 2 O 2 production act upstream of NO production during CO 2 signaling in guard cells (Shi et al ). Together, these findings suggest that ABA and ROS signaling are required to enhance high CO 2 ‐induced stomatal closure.…”
Section: Crosstalk Among Co2 Aba and Ros Signaling During Stomatal Mmentioning
confidence: 90%
“…Hence, eCO 2 alters cellular redox homeostasis as discussed previously (Mhamdi and Noctor, 2016). In addition, RBOH‐mediated ROS production facilitates lateral root emergence in Arabidopsis (Shi et al ., ; Orman‐Ligeza et al ., ). The data presented here demonstrates that RBOH1 expression in the roots of WT/ rboh1 plants had little effect on arbuscular mycorrhizal symbiosis and P uptake in response to changes in the concentration of atmospheric CO 2 compared to rboh /WT plants (Figs e,f, S6c, S7).…”
Section: Discussionmentioning
confidence: 99%
“…OST1 also interacts and phosphorylates with plasma membrane-bound N terminus of respiratory burst oxidase homolog D (RBOHD) and F (RBOHF) protein and in the guard cells of ost1 knockout mutant, the ABA-induced ROS generation is eliminated thereby suggesting that OST1 catalyzes ROS production (H 2 O 2 ) mediated by NADPH oxidase [33], [34]. Recently, Shi et al [35] reported that OST1 compromised the CO 2 -induced H 2 O 2 and NO accumulation, upregulation of SLAC1 expression, and reduced stomatal aperture.…”
Section: Ros and Stomatal Opening/closing: A Cascade Of Signaling Netmentioning
confidence: 99%